Challenges That Make/Break the Athlete's Quest to Become an Entrepreneur: A Qualitative Study About Fans' Perceptions - Hasaan Syed Ali; Nawaz Shahid; Iqbal Syed Javed; Khalid Jawaria (Sciendo, 2018)
Athletes are a new type of celebrity in the world. Following other celebrities, there are several examples of athletes who have used their persona of fame to go a step further with their so-called personal brands and actually launch products carrying their names. As athletes are considered brands in themselves, these sorts of activities (i.e., introducing a product brand) are considered as an extension of the athlete's brand. Given the nature of the research, this study employed a qualitative design. A purposeful convenience sampling technique was employed to select study participants according to a set of predetermined criteria. The final sample comprised nine fans. The fans identified five major factors that could be important in the context of an athlete's decision to start his/her own brand. The five identified factors that could decide the fate of an athlete's brand extensions were the athlete's origin, extension fit, gender, performance, and impression. According to fans, these factors play an important role in the athlete's venture as an entrepreneur. The study suggests that although fans understand that athletes are brands in themselves, Pakistani fans are not fond of the idea of athletes becoming entrepreneurs due to the fans' emotional attachment to the athletes. As this is the first study expressing fans' perspectives in the context of athlete brand extension, this study is an addition to the academic literature and theories of athlete branding and athletes as entrepreneurs.